1977
DOI: 10.1037/0096-3445.106.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and structure in visual patterns.

Abstract: A series of seven experiments investigated the determinants of judged pattern complexity, with emphasis on the identification and measurement of structural variables. In an exploratory study, it was found that the determinants of pattern complexity could be separated into quantitative variables (number of turns, amount of contour), which set an upper bound on complexity, and structural variables, which reduced perceived complexity from the upper bound value. Results indicated that a wide variety of structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
113
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 23 publications
(37 reference statements)
17
113
0
Order By: Relevance
“…Similar to the study conducted by Chipman (1977), Sakai and Inui (2000) conducted experiments involving psychological complexity estimation using a set of contours with different numbers of convex parts at a constant P/√A value. The results showed that psychological complexity was predicted by the number of convex parts rather than P/√A.…”
Section: Psychological Estimation Of the Curved Contourmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the study conducted by Chipman (1977), Sakai and Inui (2000) conducted experiments involving psychological complexity estimation using a set of contours with different numbers of convex parts at a constant P/√A value. The results showed that psychological complexity was predicted by the number of convex parts rather than P/√A.…”
Section: Psychological Estimation Of the Curved Contourmentioning
confidence: 99%
“…Real correlations between numbers of turns in BPs and P 2 /A have been shown to be very strong (Chipman, 1977). To determine which of the two physical variables was more effective with psychological complexity, Chipman (1977) conducted an estimated experiment using a set of BPs that included different numbers of turns at a constant P 2 /A value. The results showed that estimations of psychological complexity were higher for patterns with higher, relative to lower, numbers of turns, even though they all possessed constant P 2 /A values.…”
Section: Psychological Estimation Of the Curved Contourmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the goodness and the complexity of a pattern seem to be directly related not only to the amount of total symmetry but also to the amount of partial symmetry in the pattern (Chipman, 1977;Howe, 1980). Therefore, we now define a measure of partial symmetry and another related measure.…”
Section: Two-dimensional Discretewalsh Transformsmentioning
confidence: 99%
“…Although Fourier (sine-cosine) functions also have this property, they do not have the following property: The two-dimensional Walsh functions take only two values, +1 and -1. This property facilitates the compattern complexity (Chipman, 1977). It would be useful, therefore, to develop a quantitative and objective measure of symmetry in order to predict perceptual organization.…”
mentioning
confidence: 99%